PENGARUH PERAN GURU DAN KEDISIPLINAN BELAJAR SISWA TERHADAP HASIL BELAJAR FIQIH DI SMPIT MARDHATILLAH SUKOHARJO TAHUN PELAJARAN 2023/2024 - Anhanuri, Fauzan Mubarok; Nashir, Muhammad Ja’far; Abdullah, Mu’in (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
This study aims to determine the effect of the role of teachers and student learning discipline on learning outcomes in fiqh subjects at SMPIT Mardhatilah Sukoharjo. This study uses a correlational quantitative approach. This research is a quantitative study conducted at SMPIT Mardhatillah Sukoharjo with a sample size of 43 students. In this study the data was taken using a questionnaire and fiqh grade data. The technical analysis used in hypothesis testing is multiple regression analysis. The results of this study prove that this study shows that 1) There is no significant correlation between the influence of the teacher's role and student learning outcomes, with an r-count value of 0.204 which is smaller than r-table 2.021. 2) There is no significant correlation between student learning discipline and learning outcomes, with an r-count value of 0.295 which is smaller than the r-table of 2.021. 3) Simultaneously, the influence of the role of teachers and student learning discipline has a significant influence on learning outcomes in fiqh subjects at SMP IT Mardhatillah Sukoharjo in the 2023/2024 academic year, as evidenced by the significance value of 0.028 which is smaller than 0.05 and the value of F count 3.912 which is greater than F table 3.23.